The relationship between perceived trusted leader and employees' commitment - Bong, Jenny Siat Sze (University Malaysia Sarawak (UNIMAS), 2009)
This study was conducted to examine the relationship between perceived trusted leader and employees' commitment. A survey method was used to gather 72 usable questionnaires from employees who had worked in TM Point Kuching. The outcomes of hypotheses testing using Pearson Correlations had confirmed that there is a positive relationship between perceived trusted leader (integrity and competency) and employee commitment (affective commitment, continuance commitment and normative commitment). In addition, regression analysis had used to identify the best predictors of independent variables (integrity and competency) with dependent variables (affective commitment, continuance commitment and normative commitment) and the results shown that competency had been the best predictors to employees' commitment. Furthermore, the implications of this study, limitations of study and directions for future research were discussed.